Large canopy and animal‐dispersed species facilitate natural regeneration in tropical forest restoration. Issue 4 (5th June 2021) - Mendes, Lara M.; César, Ricardo G.; Uezu, Alexandre; Beltrame, Tiago P.; Rodriguez, Luiz C. E.; Gomes, Haroldo B.; Cullen, Laury
Abstract : Realizing the benefits of forest restoration requires that these ecosystems be maintained after the senescence of planted trees through facilitation of natural regeneration. We analyzed the effect of tree canopy cover, dispersal syndrome, deciduousness, and taxon in facilitating natural regeneration in tropical forest restoration planting. Canopy cover had additive positive effect on natural regeneration when combined with animal dispersal or evergreen trees. Animal dispersal had a positive effect on facilitating natural regeneration abundance, while evergreen species had a positive effect on natural regeneration richness only. Although variation within and among species was high, restoration practitioners could consider using species with these traits to facilitate natural regeneration and hence development of restoration plantings.